INTELLECTUAL CAPITAL, PROFIT SHARING RATIO, DAN CORPORATE GOVERNANCE PADA BANK UMUM SYARIAH DI INDONESIA - Tri Wahyudi (Tirtayasa Ekonomika, 2019)
This  research  is  meant  to  analyze  the  influence  of  intellectual  capital  to  the  profit sharing ratio (PSR)  of  Syariah Commercial Banks with corporate governance as the intervening variable. The population is Syariah Commercial Banks which are listed in  Bank  Indonesia in 2011-2016  periods  which is done by using the financial statement data which  has  been  obtained  by  using  purposive  sampling  and  based  on  the  determined  criteria,  so  57 (fifty seven)  samples  which have met the criteria. The analysis technique has been done by using multiple linear regressions analysis and path analysis.  Based on the result of multiple linear regressions analysis and path analysis with its significance rate is 5% so that the result of this research shows that: 1) intellectual capital has not influence to the profit sharing ratio (PSR), 2) intellectual capital has influence to the profit sharing ratio (PSR) with corporate governance as intervening variable.